(untitled) (Research, Society and Development, 2025)
The investigation aims to describe the Agroforestry System (SAF) implementation, management, and perspectives at the Sossego locality in the Municipality of Floriano, State of Piauí (PI), Brazil. This SAF primarily utilizes the plant Mimosa caesalpiniifolia (J. Bot. Hooker, 1841), commonly known as "Sabiá," with the intention of improving soil quality to enable crop rotation and promote the locality sustainable economic development. The implementation activities occured between December 2023 and January 2024 with the collaboration of students from the Biological Sciences Teaching Degree at IFPI - Floriano Campus, as part of the Curricular Extension activities in partnership with the ABC Project for Human Rights and the Diocesan and Caritas of Floriano-PI. The SAF in the Sossego locality is organized in two configurations: double rows of Sabiá, with 5 meters of distance between them, interspersed with other plants such as ipê (Handroanthus ochraceus), Aroeira (Schinus terebinthifolia Raddi), and Tingui (Magonia pubescens), and single rows; and the other with Sabiás spaced 1 meter apart. During the extension activities carried out by the students in the locality, several activities are performed to contribute to the functioning and maintenance of the SAF, including cleaning pruning, formation pruning, and guiding pruning of the Sabiá. Through this, the students enhance their theoretical and technical knowledge in a practical and applied manner, aiming to promote Sustainable Development.